IMPLEMENTATION OF THE MOBILE GAME BASED LEARNING METHOD USING THE TIMES TIME MACHINES APPLICATION TO IMPROVE STUDENT'S UNDERSTANDING ABOUT TELLING THE TIME - Afro' Desinta (Universitas Samudra, 2021)
This best practice report is based on the findings of documentation of learning outcomes in the first meeting material about Telling the Time in class VII B Semester I of the 2021/2022 academic year, out of 22 students, it was found that only 3 students could understand time in English. , while 19 other students still do not understand. Therefore, the solution to the problem in learning in the classroom is by utilizing an educational game application available on the Google Play Store, namely Timex Time Machines. The objectives of this good practice are 1) To describe students' understanding of the material about Telling the Time using the Mobile Game-Based Learning method with the Timex Time Machines application; 2) Describe the ability of students to determine the right time in learning Mobile Game-Based Learning with the Timex Time Machines application. The results of this activity: 1) Increased students' understanding of the material about telling the Time as evidenced by the GPA of 18 people; 2) The increased ability of 22 students in determining the right time is proven by completing Level One and getting an appreciation of